Locatelli and the Violin Bravura Tradition - Morabito, Fulvia (Turnhout Brepols, 2015)
The present volume investigates the violin bravura tradition in the 18th- and 19th-century Europe. 2014 witnessed the 250th anniversary of the death of two violin virtuosos: Pietro Antonio Locatelli (Bergamo 1695 Amsterdam 1764) and Jean-Marie Leclair (Lyon 1697 - Paris 1764). The influence of Locatellis output on the development of violin composition lay in the sphere of virtuosity. The present book explores the figures of Locatelli and Leclair, circumstantiating their relationships and developing new perspectives onto them. The two virtuosos provide a suitable starting-point from which to investigate the violin bravura tradition, which, beginning in Italy, spread through France and the rest of the nineteenth-century Europe. The volume thus encompasses articles dedicated to Artôt, Baillot, Guignon, Guillemain, Mondonville, Paganini, Pagin, Rode, Spohr, Tessarini, Tartini, Ysaÿe. The authors are: Sallynee Amawat, Fabrizio Ammetto, Alejandra Béjar Bartolo, Paola Besutti, Gregorio Carraro, Étienne Jardin, Walter Kurt Kreyszig, Candida Felici, Priscille Lachat-Sarrete, Simone Laghi, Alessandro Mastropietro, Fulvia Morabito, Paola Palermo, Rudolf Rasch, Renato Ricco, Rohan H. Stewart-MacDonald, Michael Talbot, Guillaume Tardif and Neal Zaslaw.
Keywords: Locatelli, Pietro Antonio -- 1695-1764; 18th Century (1701-1800); Violinist; Virtuosity